PROVISIONS AND LEGAL CONSEQUENCES OF DIVORCE FOR INDONESIAN NATIONAL ARMY, CIVIL SERVANTS AND CIVIL CITIZENS - Andrew Pradikta (UM.Tapanuli Selatan, 2025)
Divorce can be done by anyone including Civil Servants whose position as civil servants who are expected to be good examples for society can also get divorced. Basically, filing for divorce case examination for civil servants, TNI members or ordinary citizens can be filed through the Religious Court if the disputing parties are Muslim. However, if the disputing parties are not Muslim, the submission can be submitted through the District Court where the respondent is domiciled. As a scientific paper, the writing of this paper cannot be separated from the research method. The research method is a procedure, steps or procedures carried out with the aim of obtaining data, where the data obtained will be used to conduct research with certain goals and functions Divorce is one of the legal acts that can be carried out due to marriage. Marriage is regulated in Article 1 paragraph 1 of Law No. 1 of 1974 concerning Marriage. Based on the provisions stipulated in PP No. 45 of 1990 concerning amendments to PP No. 10 of 1983. According to Article 3 of PP No. 45 of 1990, , based on the provisions contained in the TNI Commander Regulation No. 11 of 2007.